2022
DOI: 10.55519/jamc-04-s4-10113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Panbiotm Covid-19 Ag Rapid Test in Sars-Cov-2 Detection: Comparison With Rt-PCR Test

Abstract: Background: Evidence on performance of Rapid Antigen Detection Tests to recognize SARS-CoV-2 symptomatic patients in our context is limited. This study was aimed to evaluate Panbio™ COVID-19 Ag Rapid Test Device (Abbott Diagnostics, Jena, Germany) in identifying SARS-CoV-2 infection in comparison with RT-PCR test. Methods: This cross-sectional validation study was carried out at Margalla Hospital, Taxila from October, 2020 to March, 2021. Three hundred and eighty-two participants of both gender and all ages, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…Differently from our study, SARS-CoV-2 diagnostics accuracy tests conducted with Panbio (Ag-RDT) and qRT-PCR in Margalla Hospital, Pakistan showed higher sensitivity (94.3 %) and lower specificity (37.9 %) [ 18 ]. This may be explained by the fact that they only included participants with symptoms in the infection's early stages (3–4 days of onset of symptoms).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Differently from our study, SARS-CoV-2 diagnostics accuracy tests conducted with Panbio (Ag-RDT) and qRT-PCR in Margalla Hospital, Pakistan showed higher sensitivity (94.3 %) and lower specificity (37.9 %) [ 18 ]. This may be explained by the fact that they only included participants with symptoms in the infection's early stages (3–4 days of onset of symptoms).…”
Section: Discussioncontrasting
confidence: 63%
“…The manufacturer reported a specificity of the Panbio COVID-19 Ag of 99.8 % (95%CI 98.65%–100 %) and an overall sensitivity of 98.1 % (95%CI: 93.2%–99.8 %). It was also reported that sensitivity is 100 % (95%CI: 92.3%–100 %) within the first three days of symptom onset and 96.6 % (95%CI: 88.1%–99.6) 4–7 days after symptom onset [ 15 ] [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Methodsmentioning
confidence: 99%
“…Most of the tests are characterized by high specificity while sensitivity seems to vary. On the contrary, the Panbio COVID-19 Ag RAT showed high sensitivity (94.3%) and very low specificity (39.7%) [11].…”
Section: Discussionmentioning
confidence: 88%
“…This was similar to the studies reported in Ethiopia (74.2%) (13), Valencia, Spain (79.6%) (14), Madrid, Spain (73.3%) (15), Switzerland (81%) (16), Brazil (84%) (17), Geneva University Hospital (85.5%) (18), Marseille, France (75.5%) (19), Sint Maarten, Dutch Caribbean (84%) (20), and Vienna (73.33%) (6). But it was lower than the sensitivity reports at Margalla Hospital, Taxila (94.3%), and Spain (90.5%), which might be due to all study participants having short-duration symptoms (21). However, the current finding is lower than the 91.4% sensitivity of the test reported by the manufacturers (10).…”
Section: Discussionmentioning
confidence: 94%